Teaching triangle rigidity to k-12 students with applications to civil engineering - Lamas, Rita De Cassia Pavan [UNESP]; Lozada-Cruz, German [UNESP]; Peixoto, Aruquia (Institute of Electrical and Electronics Engineers (IEEE), 2020)
In this work, we propose a concrete material to incite the student to conjecture the cases of congruence of triangles and to motivate them to apply this knowledge in Engineering, in particular, the use of polygon rigidity, named triangle, in civil construction. An extension of the material to the cases of similarity of triangles and other polygons also aims applications in this area, among them, calculation of inaccessible heights and mockup building.
Keywords: Attracting students to STEM; Civil Engineering; Congruence and similarity of triangles; K-12